2016
DOI: 10.1186/s12944-016-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

APOC3 induces endothelial dysfunction through TNF-α and JAM-1

Abstract: BackgroundThe fatality rate for cardiovascular disease (CVD) has increased in recent years and higher levels of triglyceride have been shown to be an independent risk factor for atherosclerotic CVD. Dysfunction of endothelial cells (ECs) is also a key factor of CVD. APOC3 is an important molecule in lipid metabolism that is closely associated with hyperlipidemia and an increased risk of developing CVD. But the direct effects of APOC3 on ECs were still unknown. This study was aimed at determining the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…This process is mediated by several independent pathways, including SR-A, class B (CD36), and LOX-1 [ 23 25 ] . Pro-inflammatory genes (TNF-α and IL-6) were reported to be expressed at high levels and to contribute to cardiovascular diseases caused by hyperlipidemia [ 26 , 27 ] .…”
Section: Discussionmentioning
confidence: 99%
“…This process is mediated by several independent pathways, including SR-A, class B (CD36), and LOX-1 [ 23 25 ] . Pro-inflammatory genes (TNF-α and IL-6) were reported to be expressed at high levels and to contribute to cardiovascular diseases caused by hyperlipidemia [ 26 , 27 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ACCENTUATE study with evacetrapib [134] showed that, although the treatment increased cholesterol efflux capacity, it also generated HDL particles with increased apoC-III content. ApoC-III-enriched HDL are less functional [135,136] and might perhaps provide apoC-III to the arterial wall, which may trigger an inflammatory process in endothelial cells, characterized by increased expression of pro-inflammatory cytokines and increased adhesion of monocytes, as well as alterations of endothelial apoptosis [135,[137][138][139]. These findings suggest that, although effective in improving the overall lipid profile, pharmacological CETP inhibition might not associate to a vascular protective effect.…”
Section: Defective Hdl Remodellingmentioning
confidence: 99%
“…Studies have also suggested that TNF-α concentrations are positively associated with VLDL-C concentrations [ 84 ], which also can be found in the PTH rabbits [ 59 ]. A recent study has showed TNF-α overexpression increased expression of JAM-1, which promoted the chemotaxis and exudation of cells to cause atherosclerosis [ 85 ].…”
Section: The Possible Mechanism Of Trls Atherogenicitymentioning
confidence: 99%